Quantification of the typical weekly in-season training load in elite junior soccer players - Wrigley, R.; Drust, B.; Stratton, G.; Scott, M.; Gregson, W. (Journal of Sports Sciences, 2012)
We examined the typical weekly training load experienced by elite junior soccer players during the in-season competitive period. Altogether, eight under-14 (U14), eight under-16 (U16) and eight under-18 (U18) players were monitored over a 2-week period during the first month of the 2010?11 competitive season. This time period included one competitive match per week. Physiological loading was monitored using heart rate (HR) and ratings of perceived exertion (RPE). Training and match loads were calculated by multiplying the global session RPE and duration (session-RPE). Total weekly training load (training and match) increased with age (U14, 2524±128 arbitrary units [AU]; U16, 2919±136 AU; U18, 3948±222 AU; P<0.05). Differences in the daily training load across the training week were also evident in the older age group relative to both U14 and U16. The amount of time engaged in low (<50% HRmax) and high (>90% HRmax) intensity activity during training and match-play was significantly lower and higher respectively in the U18 compared to the U14 group (P<0.05). When comparing activity, the intensity (% HRmax) of field training (U18, 69±2%; U16, 74±1%; U14, 74±2%) was significantly lower compared to match-play (U18, 81±3%; U16, 84,±2%; U14, 83±2) across all age groups (P < 0.05). Findings demonstrate that age related differences in the volume and intensity of weekly in-season training load are evident amongst elite professional junior soccer players. These differences may reflect a systematic approach to the long-term physical development of elite junior players.